Clinical genetics of craniosynostosis - Wilkie, A; Johnson, D; Wall, S (Lippincott, Williams & Wilkins, 2017)
Purpose of review When providing accurate clinical diagnosis and genetic counselling in craniosynostosis, the challenge is heightened by knowledge that etiology in any individual case may be entirely genetic, entirely environmental, or anything in between. This review will scope out how recent genetic discoveries from next-generation sequencing have impacted on the clinical genetic evaluation of craniosynostosis. Recent findings Survey of a 13-year birth cohort of patients treated at a single craniofacial unit demonstrates that a genetic cause of craniosynostosis can be identified in one quarter of cases. The substantial contributions of mutations in two genes, TCF12 and ERF, is confirmed. Important recent discoveries are mutations of CDC45 and SMO in specific craniosynostosis syndromes, and of SMAD6 in non-syndromic midline synostosis. The added value of exome or whole genome sequencing in the diagnosis of difficult cases is highlighted. Summary Strategies to optimise clinical genetic diagnostic pathways by combining both targeted and next-generation sequencing are discussed. As well as improved genetic counselling, recent discoveries spotlight the important roles of signalling through the bone morphogenetic protein and hedgehog pathways in cranial suture biogenesis, as well as a key requirement for adequate cell division in suture maintenance.